PENGEMBANGAN HERBARIUM BERBASIS TUMBUHAN DALAM UPACARA ADAT BROKOHAN BAYI DI KABUPATEN JOMBANG - Huda, Achmad Miftahul; Ami, Mucharommah Sartika (Universitas KH. A. Wahab Hasbullah, 2021)
learning media experts on plant-based herbariums in the Brokohan Baby traditional ceremony in Jombang Regency. The method used is development research with the R&D model as a reference. Researchers only use the first five steps in the R&D model, namely potential and problems, data collection, product design, design validation, and design revision. Interview guides were used to collect data on the types of plants used in the traditional ceremony of Brokohan Baby in Jombang Regency. The expert validation sheet was used to determine the feasibility of the herbarium developed based on the assessment of herbarium experts and learning media experts. The assessment aspects in the validation sheet are adjusted to the expertise of each expert. The data analysis technique used in this research is descriptive analysis. The results showed that the herbarium developed obtained a value of 80.00 from herbarium experts so that it met the criteria of being quite feasible. The assessment of learning media experts shows the number 95.00 with very decent criteria.